METAPHORS OF FISH NAMES IN INDONESIAN - Wijana, I Dewa Putu (Widyaparwa, 2024)
This article aims at describing metaphors of fish names in Indonesian. The study is focused on the language origin and constituent structure of the fish names,  locus of metaphorical expressions, source domains and target domains intended to, sociocultural factors which influence the metaphorical fish naming. The data are firstly collected intuitively from the researcher’s own knowledge as an Indonesian native speaker, and they are added with ones found in “Big Indonesian Dictionary” and You Tube. The data are further classified in line with the five matters that become focus of the paper consideration. Having analyzed the data carefully, the research finds that the structure of fish names may consist of two, three, four, and at maximum five elements in which ikan ‘fish’ functions as the head constituent structure. The metaphorical expressions might be located in the second, third, second and third, fourth, and so far are not found in the fifth elements. The source domains are taken from everything familiar with human life, and intended to compare on the basis of similarities and closeness with the body shape, parts of the body organs, scale color,  liquid substance produced by the aquatic animals. Many of the source domains are universals, and several of them are culture specific.Artikel ini bertujuan untuk memerikan metafora nama-nama ikan dalam bahasa Indonesia. Kajian dipusatkan pada asal bahasa dan struktur konstituen nama-nama ikan, letak satuan metaforis, ranah sumber dan ranah target metafora, dan faktor-faktor sosiokultural yang mempengaruhi penamaannya. Data-data pertama kali dikumpulkan secara intuitif dari pengetahuan penulis sebagai penutur asli bahasa Indonesia, dan dilengkapi dengan data yang dikumpulkan dari Kamus Besar Bahasa Indonesia dan You Tube. Data-data kemudian diklasifikasikan berdasarkan lima persoalan yang dijadikan fokus permasalahan. Adapun ke- lima persoalan itu adalah asal bahasa dan struktur konstituen nama-nama ikan, letak ekspresi metaforis nama-nama ikan, ranah sumber dan ranah target ekspresi metaforis nama-nama ikan, dan faktor-faktor sosiokultural yang mempengaruhi penamaan ikan. Lewat pengamatan dan analisis data secara saksama didapatkan bahwa struktur nama-nama ikan yang diambil dari berbagai bahasa terdiri dari dua sampai dengan lima elemen, dan kata ikan merupakan unsur pusatnya. Elemen mataforis dapat ditempatkan pada elemen kedua, ketiga, kedua dan ketiga, keempat, dan tidak pernah pada unsur kelima. Ranah sumber matafora penamaannya diambilkan dari segala sesuatu yang akrab dengan kehidupan manusia, dan perbandingannya berdasarkan kesamaan dan kedekatan dengan bentuk tubuh, bagian tubuh, warna sisik, cairan yang dihasilkan oleh binatang air ini. Sebagian besar ranah sumber besifat universal, dan beberapa di antaranya bersifat spesifik dan terikat budaya.